2012
DOI: 10.1002/cbdv.201200051
|View full text |Cite
|
Sign up to set email alerts
|

Composition of n‐Alkanes in Natural Populations of Pinus nigra from Serbia – Chemotaxonomic Implications

Abstract: This is the first report on the composition and variability of the needle-wax n-alkanes in natural populations of Pinus nigra in Serbia. Samples of 195 trees from seven populations belonging to several infraspecific taxa (ssp. nigra, var. gocensis, ssp. pallasiana, and var. banatica) were analyzed. In general, the size of the n-alkanes ranged from C(16) to C(33) , with the exception of ssp. nigra, for which it ranged from C(18) to C(33) . The most abundant were C(23) -, C(25) -, C(27) -, and C(29) -alkanes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…Interestingly, Bojović et al . detected short‐chain n ‐alkanes (C 16 – C 20 ) in P. nigra needle waxes, although with the smallest amount comparing to mid‐ and long‐chain n ‐alkanes. In the investigated P. nigra needles, the most abundant wax compounds were the four odd numbered n ‐alkanes C 27 , C 25 , C 23 , and C 29 (mean contents of 19.7, 18.1, 10.8, and 10.2%, resp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, Bojović et al . detected short‐chain n ‐alkanes (C 16 – C 20 ) in P. nigra needle waxes, although with the smallest amount comparing to mid‐ and long‐chain n ‐alkanes. In the investigated P. nigra needles, the most abundant wax compounds were the four odd numbered n ‐alkanes C 27 , C 25 , C 23 , and C 29 (mean contents of 19.7, 18.1, 10.8, and 10.2%, resp.…”
Section: Resultsmentioning
confidence: 99%
“…Predomination of the same four n ‐alkanes in P. nigra needle waxes was also reported by Bojović et al . , but in slightly different order (C 25 , C 27 , C 29 , and C 23 ). Moreover, these four n ‐alkanes appear to be common in different Pinus species, e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the results of previous studies have shown, all mentioned compounds could be used in chemotaxonomy as more or less relevant biomarkers in order to understand relations between plant members at different levels of plant classification. By improving the analyzing techniques (primarily GC/MS and NMR), as well as the methods of data processing (multivariate statistical analyses), a lot of chemotaxonomic studies have been used to identify and quantify wax components to prove or improve the existing classification within studied taxonomic rank . Since a lot of taxonomy studies were interested in wax constituents as reliable taxonomic markers, triterpenoids have taken a special place for many reasons.…”
Section: Introductionmentioning
confidence: 99%